2023
DOI: 10.1007/s00392-023-02263-8
|View full text |Cite
|
Sign up to set email alerts
|

New-onset atrial fibrillation after percutaneous patent foramen ovale closure: a meta-analysis

Abstract: Background The exact incidence and predictors of new-onset atrial fibrillation (AF) after percutaneous closure of patent foramen ovale (PFO) are unknown. Objective We sought to find post-procedural AF incidence rates and differences due to different screening strategies and devices. Methods A systematic search was conducted in Cochrane, MEDLINE and EMBASE. Controlled trials fulfilling the inclusion criteria were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The lack of consensus about recurrent CVEs and AF occurring after PFO closure, and the detection of different incidences in follow-ups with ECG, Holter, and event recorder, make it necessary to use simpler and common parameters. [4][5][6] The electrocardiographic parameters related to PW characteristics-specifically PWmax, PWmin, PWdis, PWPT, and PWPTF -provide valuable insights into their potential associations with AF. 25 These parameters serve as important markers of atrial electrophysiology, offering a window into the underlying substrate that may contribute to the initiation and maintenance of AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of consensus about recurrent CVEs and AF occurring after PFO closure, and the detection of different incidences in follow-ups with ECG, Holter, and event recorder, make it necessary to use simpler and common parameters. [4][5][6] The electrocardiographic parameters related to PW characteristics-specifically PWmax, PWmin, PWdis, PWPT, and PWPTF -provide valuable insights into their potential associations with AF. 25 These parameters serve as important markers of atrial electrophysiology, offering a window into the underlying substrate that may contribute to the initiation and maintenance of AF.…”
Section: Discussionmentioning
confidence: 99%
“…However, some large-scale studies have observed an increase in atrial tachycardias postclosure when compared to patients undergoing medical monitoring. 4 While this rate was observed to be 4-6% in follow-ups of symptomatic patients and ambulatory Holter analyses, it was reported to be much higher in intracardiac recording studies. Among these atrial tachycardias, atrial fibrillation (AF) is of particular importance.…”
Section: Introductionmentioning
confidence: 95%
“…The incidence was between 3.3% and 15% in high‐quality screening studies, between 0.4% and 10.3% in opportunistic studies, and between 0.2% and 4.3% in low‐quality screening studies. 28 Surely, the prospective, multicenter, observational cohort study in France will exact more safe conclusions, by monitoring 250 patients with intracardiac monitoring 2 months before and 24 months after PFO closure. 29 Although the precise incidence of AF following PFO closure remains elusive, our efforts to delineate this phenomenon are encapsulated in Figure 2 .…”
Section: Incidence Of Postprocedural Afmentioning
confidence: 99%
“… 38 This theory could probably explain why the incidence of AF was higher after the placement of first‐generation, more bulky devices, such as the STARFlex device. 28 , 39 Finally, it has been hypothesized that the interatrial conduction, largely via the Bachmann bundle lying in the roof of the atrium at the superior margin of the fossa ovalis, may be compromised by device placement. This is reflected in the finding of an increased P ‐wave duration index after closure and may provide further substrate for arrhythmogenesis.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation